Estimation of the investment function for the Republic of Macedonia - Biljana Petkovska (National Bank of the Republic of Macedonia, 2008)
Investment is one of the crucial macroeconomic variables - it adds to the capital stock and thus determines the long term production capacity in the economy. Investment, also, is one of the channels through which macroeconomic policies, monetary and fiscal policy, can affect the real economy. This paper presents an estimate of the investment function for the Republic of Macedonia, based on the Johansen cointegration technique. The results obtained show that, according to the Keynesian accelerator theory, investments are driven by changes in the aggregate demand. In addition, as the neoclassical model predicts, the cost of employing additional unit of capital exhibits significant influence on the investment decisions' of the firms, but only in the short run. The obtained results are broadly in line with the ones found in different studies and with the one used in previous work on this topic for Macedonia.
Keywords: 330; Investitionsfunktion; Kointegration; Gesamtwirtschaftliche Nachfrage; Volkswirtschaftliche Investitionstheorie; Mazedonien